A rice PHD‐finger protein OsTITANIA, is a growth regulator that functions through elevating expression of transporter genes for multiple metals. (26th November 2018) - Tanaka, Nobuhiro; Uraguchi, Shimpei; Kajikawa, Masataka; Saito, Akihiro; Ohmori, Yoshihiro; Fujiwara, Toru
Summary: Essential metal absorption for plant growth is mediated predominantly by metal‐specific transporters, with expression that responds to the environmental or cellular conditions of specific metals. Differing from metal‐specific regulation, we describe a constitutively expressed transcription factor that regulates the transport of several metals in rice. We characterized the rice mutant LOW CADMIUM 5 (LC5), which exhibited reduced growth and accumulation of essential metals (e.g., copper [Cu], zinc [Zn] and manganese [Mn]) in shoots. LC5 was dwarf and developed less tillers than the wild type, but the structure of vasculature was apparently normal. Molecular genetic analysis revealed that the causal gene of LC5 is an ortholog of the transcriptional regulator Arabidopsis thaliana TITANIA ( TTA ), known as a transcriptional regulator. Expression analyses demonstrated that the OsTTA gene encodes a nucleus‐localized protein containing a plant homeodomain‐finger (PHD‐finger) domain and is expressed ubiquitously in rice plants. RNA sequencing and quantitative PCR analyses revealed that the mRNA accumulation of transporter genes for essential metals, including iron (Fe), Zn, or Mn, were substantially lower in LC5 roots than in the wild type. Unlike known transcription factors of metal transport regulation, OsTTA transcript accumulation was not affected by metal availability. In addition, the growth defect of LC5 was partially rescued by Fe, Zn, or Mn supplementation, respectively. Taken together, OsTTA is a constitutively expressed regulator of multiple metal transporter genes responsible for essential metals delivery to shoots for their normal growth. Significance Statement: The appropriate absorption of metal nutrients is essential for plant development and important for human nutrition. In this report, we have identified a transcriptional regulator OsTTA involved in uptake of multiple metals through the activation of metal transporter genes, irrespective of metal conditions. Our findings suggest a presence of a constitutive mechanism that activate transport of several metals to shoots and provide insight into effective use of metals in rice and for biofortification.